The Development and Validation of a Local Wisdom-Integrated Physics Module to Grow the Students’ Character of Sanggup Bagawi Gasan Masyarakat - Misbah Misbah; Maya Hirani; Syubhan Annur; Nurul F Sulaeman; Mohd Ali Ibrahim (STKIP Singkawang, 2020)
This study is aimed to describe the feasibility of a local wisdom-integrated physics module to train the character of sanggup bagawi gasan masyarakat, viewed from the aspect of validity, practicality, effectiveness, and the achievement of student’s character. This physics module is integrated to the production of brown sugar in Balangan Regency, on temperature and heat materials. This research is a research development with ADDIE design. The subjects of this research were 27 students of class X in one of the high schools in Balangan. The research instruments used included were validation sheets, student response questionnaires, learning achievement test, and character observation sheets. The result shows that developed physics module has a good aspect of validity, good practicality, moderate effectiveness, and it is very good on training student’s character. It is concluded that physics module which is integrated to the local wisdom to train the character of sanggup bagawi gasan masyarakat is feasible to use on temperature and heat materials.This study is aimed to describe the feasibility of a local wisdom-integrated physics module to growthe character of sanggup bagawi gasan masyarakat, thatviewed from the aspect of validity, practicality, effectiveness, and the achievement of student’s character. This module is integrated to the production of brown sugar in Balangan Regency, as a local activity that related to heat and temperature materials. This research is a research development with ADDIE design. The subjects of this research were 27 students of class X in one of the high schools in Balangan. The research instruments were validation sheets, student response questionnaires, learning achievement test, and character observation sheets. The result shows that physics module has a good aspect of validity, good practicality, moderate effectiveness, and it is very good on training student’s character. Physics module which isintegrated to the local wisdom to growthe character of sanggup bagawi gasan masyarakat is feasible to use on heat andtemperature materials.